2010
DOI: 10.1523/jneurosci.1520-10.2010
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Necrosis Factor-α (TNF-α) Regulates Shedding of TNF-α Receptor 1 by the Metalloprotease-Disintegrin ADAM8: Evidence for a Protease-Regulated Feedback Loop in Neuroprotection

Abstract: Tumor necrosis factor ␣ (TNF-␣) is a potent cytokine in neurodegenerative disorders, but its precise role in particular brain disorders is ambiguous. In motor neuron (MN) disease of the mouse, exemplified by the model wobbler (WR), TNF-␣ causes upregulation of the metalloprotease-disintegrin ADAM8 (A8) in affected brain regions, spinal cord, and brainstem. The functional role of A8 during MN degeneration in the wobbler CNS was investigated by crossing WR with A8-deficient mice: a severely aggravated neuropatho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
56
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(59 citation statements)
references
References 42 publications
(48 reference statements)
2
56
1
Order By: Relevance
“…1a). TNFR1 has been shown to undergo ADAM17-and ADAM8-mediated cleavage, resulting in the release of sTNFR1 ectodomains and generation of a membrane-anchored TNFR1 CTF (38,64). The majority of known ␥-secretase substrates also undergo ectodomain shedding in the extracellular domain as a prerequisite for ␥-secretase-mediated cleavage of the remaining membrane-bound CTF.…”
Section: Ectodomain Shedding Is a Prerequisite For ␥-Secretasementioning
confidence: 99%
See 1 more Smart Citation
“…1a). TNFR1 has been shown to undergo ADAM17-and ADAM8-mediated cleavage, resulting in the release of sTNFR1 ectodomains and generation of a membrane-anchored TNFR1 CTF (38,64). The majority of known ␥-secretase substrates also undergo ectodomain shedding in the extracellular domain as a prerequisite for ␥-secretase-mediated cleavage of the remaining membrane-bound CTF.…”
Section: Ectodomain Shedding Is a Prerequisite For ␥-Secretasementioning
confidence: 99%
“…TACE/ADAM17, a member of the A disintegrin and metalloprotease (ADAM) family of transmembrane and secreted proteases, is responsible for ectodomain shedding of TNFR1 (38,39). Recently, it has emerged that several proteins that undergo ectodomain shedding are subsequently cleaved by the ␥-secretase protease (40 -42).…”
mentioning
confidence: 99%
“…valuable model for many aspects of neurodegeneration, including neuroinflammatory processes [13]. The WR mouse is also widely employed for evaluating novel treatment options to counteract symptoms of ALS [14].…”
Section: Introductionmentioning
confidence: 99%
“…PMA induces the shedding by activating ADAM17, whereas ionomycin, an agent causing extracellular Ca 21 influx, induces it by activating ADAM10 (Nagano et al, 2004). So far, ADAMs 17 and 8, but not ADAM10, are known to cleave the extracellular domain of TNFR1 (Bell et al, 2007;Bartsch et al, 2010). In most studies, ADAM17 has been identified as a TNFR1 sheddase, but ADAM8 was responsible for shedding of TNFR1 in the isolated primary neurons and microglia stimulated with TNF-a (Bartsch et al, 2010).…”
mentioning
confidence: 99%
“…So far, ADAMs 17 and 8, but not ADAM10, are known to cleave the extracellular domain of TNFR1 (Bell et al, 2007;Bartsch et al, 2010). In most studies, ADAM17 has been identified as a TNFR1 sheddase, but ADAM8 was responsible for shedding of TNFR1 in the isolated primary neurons and microglia stimulated with TNF-a (Bartsch et al, 2010). Because ADAM17 cleaves TNFR2 as well as TNFR1 (Saftig and Reiss, 2011), shedding of TNFR1, but not TNFR2 by 1,25D 3 in the present study, suggests that ADAM17 is not the responsible sheddase.…”
mentioning
confidence: 99%